New Inhibitors of Glucose-6-Phosphate Dehydrogenase Discovered by Molecular Docking - Haitham Al-Madhagi; Hisham Al-Ward (PT FORMOSA CENDEKIA GLOBAL, 2022)
The aim of this study is to in silico screen new glucose-6-phosphate dehydrogenase (G6PD) inhibitors. glucose-6-phosphate dehydrogenase is the first and regulator of pentose phosphate pathway providing NADPH and ribose-5-phosphate required for various syntheses from fatty acids to DNA. G6PD is linked to oxidative stress and hence, to inflammation as well. Therefore, G6PD inhibition is a useful target against inflammation, cancer and some infections. Virtual screening of 15 ligands in the NADP-binding site in comparison with the standard inhibitor 6-aminonicotinamide using iGEMDOCK. Besides, ADME properties of the selected compounds were performed via SWISSADME webserver. All the tested ligands were better than reference inhibitor in terms of binding energy as well as pharmacokinetic and ADME parameters. Moreover, of all tested compounds, ligand 15 showed best docking fitness (-115 Kcal/mole total energy). Novel compounds were screened to be lead inhibitors of G6PD enzyme and ligand 15 ranked first.